Orbit : NASA Astronauts Photograph the Earth - Apt, Jay ; Helfert, Michael and Wilkinson, Justin; Edited by Ressmeyer, Roger (Washington National Geography Society, 1996)
Collects many of the most visually significant photographs taken during the first forty-one years of orbital space travel, in a volume that reflects the achievements of the space program, the natural wonders of the planet, and the consequences of pollution. Reprint
Include Color Illustration and Index
Keywords: Earth (Planet) -- Space photography